Src Family Kinases Mediate Betel Quid-Induced Oral Cancer Cell Motility and Could Be a Biomarker for Early Invasion in Oral Squamous Cell Carcinoma - Chen, Jeff Yi-Fu (Neoplasia Press Inc., 2008)
Betel quid (BQ)-chewing oral cancer is a prevalent disease in many countries of Southeast Asia. Yet, the precise disease mechanism remains largely unknown. Here, we show that BQ extract-induced cell motility in three oral cancer cells (Ca9-22, SAS, and SCC9) presumably involves the Src family kinases (SFKs). Besides, BQ extract can markedly induce cell migration of wild type mouse embryonic fibroblasts (MEFs) but not MEFs lacking three SFK members, namely, Src, Yes, and Fyn, indicating the requirement of SFKs for BQ-induced cell motility. Betel quid extract can also elevate cellular SFK activities because phosphorylation of tyrosine 416 at the catalytic domain is increased, which in turn promotes phosphorylation of an in vitro substrate, enolase. Furthermore, we identified that areca nut, a major component of BQ, is the key factor accounting for BQ-induced cell migration and invasion through SFKs-mediated signaling pathways. Immunohistochemistry revealed that, particularly in BQ-chewing cases, the activity of SFKs was significantly higher in tumor-adjacent mucosa than that in solid tumor areas (P < .01). These results suggest a possible role of SFKs in tumor-host interface and thus in early tumor invasion in vivo. Consistent with this is the observation that activation of SFKs is colocalized with invasive tumor fronts in oral squamous cell carcinoma. Together, we conclude that SFKs may represent a potential biomarker of invasion and therapeutic target in BQ-induced oral cancer.